SSIM-based error-resilient rate-distortion optimization of H.264/AVC video coding for wireless streaming - Zhao, Pinghua; Liu, Yanwei; Liu, Jinxia; Ci, Song; Yao, Ruixiao (Signal processing. Image communication, 2014)
The SSIM-based rate-distortion optimization (RDO) has been verified to be an effective tool for H.264/AVC to promote the perceptual video coding performance. However, the current SSIM-based RDO is not efficient for improving the perceptual quality of the video streaming application over the error-prone network, because it does not consider the transmission induced distortion in the encoding process. In this paper, a SSIM-based error-resilient RDO scheme for H.264/AVC is proposed to improve the wireless video streaming performance. Firstly, with the help of the SSE-based RDO, we present a low-complexity Lagrange multiplier decision method for the SSIM-based RDO video coding in the error-free environment. Then, the SSIM-based decoding distortion of the user end is estimated at the encoder and is correspondingly introduced into the RDO to involve the transmission induced distortion into the encoding process. Further, the Lagrange multiplier is theoretically derived to optimize the encoding mode selection in the error-resilient RDO process. Experimental results show that the proposed SSIM-based error-resilient RDO can obtain superior perceptual video quality (more structural information) to the traditional SSE-based error-resilient RDO for wireless video streaming at the same bit rate condition.